Gestión de los bienes propios en la sociedad de gananciales: una visión crítica - Santillán Santa Cruz, Romina (2020)
Community of property is a regime of relative community. It is legally configured by the existence of the common property of the spouses, although each spouse could retain the personal property. Thus, complicated legal situations may arise as a result of the management of such property. The management of the personal property is chaired by the rule of spouses’ freedom of action. For this motive, there are no explicit limits to the Administration and disposal of that property. However, this does not imply there are no limits to their actions.In this article, the author seeks to point on the study of the legal restrictions and implicit limits that would be applicable to the management of the personal property in the community of property in the Peruvian legal framework. She also analyses the concept of unilateral unrenounceability of acts of liberality because it appears to be the only exception to the rule of freedom of action.